2005
DOI: 10.1038/sj.ejcn.1602132
|View full text |Cite
|
Sign up to set email alerts
|

The effects of conjugated linoleic acid supplementation on immune function in healthy volunteers

Abstract: Objective: To assess the effects of dietary supplementation using two isomeric blends of conjugated linoleic acid (CLA) on immune function in healthy human volunteers. Design: Double-blind, randomised, placebo-controlled intervention trial. Subjects and intervention: A total of 55 healthy volunteers (n ¼ 20 males, n ¼ 35 females) were randomised into one of three study groups who received 3 g/day of a fatty acid blend containing a 50:50 cis-9, trans-11: trans-10, cis-12 CLA isomer blend (2 g CLA), and 80:20 ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 44 publications
(72 reference statements)
4
48
1
Order By: Relevance
“…However, dietary CLA increased the IL-2 production of peripheral blood lymphocytes and alleviated the inhibitory effect of CsA injection on IL-2 inductive activity (P < 0.01). Several studies in humans, poultry and rats have shown that dietary CLA increased IL-2 activity induced by Con A (Wong et al, 1997;Nugent et al, 2005;Takahashi et al, 2007). IL-2 messenger RNA expression levels in the CLA diet group were significantly higher than in the control group in a pig model of PCV2-induced immunosuppression (Lee et al, 1994).…”
Section: Discussionmentioning
confidence: 98%
“…However, dietary CLA increased the IL-2 production of peripheral blood lymphocytes and alleviated the inhibitory effect of CsA injection on IL-2 inductive activity (P < 0.01). Several studies in humans, poultry and rats have shown that dietary CLA increased IL-2 activity induced by Con A (Wong et al, 1997;Nugent et al, 2005;Takahashi et al, 2007). IL-2 messenger RNA expression levels in the CLA diet group were significantly higher than in the control group in a pig model of PCV2-induced immunosuppression (Lee et al, 1994).…”
Section: Discussionmentioning
confidence: 98%
“…It has been shown that both the cis-9,trans-11 and the trans-10,cis-12 isomers reduce TNF-a levels in macrophage cell line and in mice (Akahoshi et al, 2002;Bhattacharya et al, 2005;Pariza et al, 2000;Park et al, 2003;Sugano et al, 2001;. Effects of CLA on TNF-a levels in human studies, however, were less consistent (Albers et al, 2003;Nugent et al, 2005;Smedman, Basu, Jovinge, Fredrikson, & Vessby, 2005;Song et al, 2005). Recently, it was reported that cis-9,trans-11 and trans-10,cis-12 isomers cause different inflammatory responses and these results suggest a possible link to modified inflammatory responses by CLA and insulin resistance as well (Poirier, Shapiro, Kim, & Lazar, 2006;Ramakers, Plat, Sebedio, & Mensink, 2005).…”
Section: Safety and Health Considerationsmentioning
confidence: 95%
“…However, the sample size was small, at seventeen. In a larger study, with fifty-five subjects, Nugent et al (138) found that either a 50:50 CLA mixture or an 80:20 CLA mixture at about 2 g/d had minimal effects on lymphocytes and cytokines, and had no additional benefit on immune function compared with linoleic acid. CLA supplementation has also been linked to reduced symptoms of birch pollen allergy (104) and improved airway hyper-responsiveness in asthmatics (132) .…”
Section: Conjugated Linoleic Acid Inflammation and Immune Effectsmentioning
confidence: 99%